Development of Abatar Interactive Multimedia (Build Flat Application) to Increase Students' Interest in 4th Grade Mathematics - Rachmah, Difani Fulan Maulidiyah; Annisa, Choirul; Rohmawati, Aulia (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The nation's standard of living is impacted by education. Therefore, it is essential to raise educational standards. In order to boost students' interest in studying, this study intends to create interactive learning media in the form of an application named Abatar Interactive Multimedia (Build Flat Application). R&D (research and development) is the methodology employed, along with the APPED development model. Interactive Learning Multimedia called Abatar, which has undergone a validity test, is the outcome of this study. The average score for the media validation test, which included input from professionals in media design, content, learning, and user testing, was 90.13% in the Valid category. However, studies on pupils revealed a 33% boost in their interest in learning. This demonstrates that Abatar Interactive Multimedia is useful for instruction and can boost students' attention in MI Hidayatus Shibyan's class 4A.